Urodynamic characteristics might be variable in bladder pain syndrome/interstitial cystitis patients with different non‐bladder co‐morbid conditions. Issue 3 (March 2018) - Cheng, Wei‐Ming; Fan, Yu‐Hua; Lin, Alex T.L.
Abstract : Background: : The aim of the study was to identify the impact of non‐bladder co‐morbid conditions on the urodynamic characteristics of patients with bladder pain syndrome/interstitial cystitis. Methods: : Patients with bladder pain syndrome/interstitial cystitis completed the screening questionnaires for chronic fatigue syndrome, irritable bowel syndrome, fibromyalgia, temporo‐mandibular disorders, multiple chemical sensitivities, tension/migraine headache, and localized myofascial pain disorder. They underwent either conventional pressure‐flow urodynamic studies or video‐urodynamic studies. Urodynamic variables were compared between patients with and those without co‐morbid conditions. Results: : Of 111 patients (16 males and 95 females) with bladder pain syndrome/interstitial cystitis, 87 (78.4%) had at least one co‐morbid condition (62% males vs 82% females, p = 0.005). Those with concomitant irritable bowel syndrome were younger and had urodynamic characteristics of smaller catheter‐free voided volume, lower catheter‐free average flow rate, smaller bladder volume on the first desire to void, and more prevalent dysfunctional voiding than those without irritable bowel syndrome. Patients with concomitant localized myofascial pain disorder also had larger bladder volume at the first desire to void and lower pressure at maximum flow than those without co‐morbid myofascial pain disorder. There were no significant differences in urodynamic parameters between bladder pain syndrome/interstitial cystitis patients with and those without other co‐morbidities. Conclusion: : Bladder pain syndrome/interstitial cystitis patients, especially females, are more likely to have non‐bladder co‐morbidities, especially tension/migraine headache and localized myofascial pain. Bladder pain syndrome/interstitial cystitis Patients with co‐morbid irritable bowel syndrome are younger and more likely to have abnormal urodynamic findings.